Pain Intensity and Risk of Bone Fracture in Children With Minor Extremity Injuries. - Zanchi, Chiara; Giangreco, Manuela; Ronfani, Luca; Germani, Claudio; Giorgi, Rita; Calligaris, Lorenzo; Norbedo, Stefania; Liccari, Giulio; Cozzi, Giorgio; Barbi, Egidio (Pediatr Emerg Care, 2018)
OBJECTIVES: Injuries are one of the most common causes of pediatric emergency department (ED) visit. The aim of this study was to investigate the relationship between the intensity of pain at the ED visit of children presenting with an extremity injury and the risk of fracture. METHODS: We conducted a retrospective study, considering all patients presenting to the ED of a children's hospital in Italy, with an accidental extremity injury, between May and December 2015. We selected all children aged 8 to 17 years who underwent an x-ray. Children with major, multiple, or nonextremity injuries were excluded. Age, sex, spontaneous and palpation pain, local swelling, time between injury, and medical evaluation were recorded. Sensibility and specificity of spontaneous and palpation pain in detecting a fracture were calculated. RESULTS: We reviewed 994 medical records; of these, 344 (34.6%) reported a fracture. Children's median age was 12 years (interquartile range [IQR], 10-14). Median spontaneous pain at the ED visit was not significantly different between children with and without a fracture: 4.0 (1.0-6.0) and 5 (1.0-6.0), respectively (P = 0.129). Children with mild palpation pain and children without an increase of pain of at least 2 points between spontaneous and palpation pain were fractured in 3.2% and 0.97% of cases, respectively. CONCLUSIONS: In this series, pain intensity in children with a minor extremity injury was not a good marker of fracture. Nevertheless, children with mild palpation pain or with a mild increase of pain between spontaneous and palpation pain had a low risk of fracture.

A premenarcheal girl with urogenital bleeding. - Lora, Angela; Scrimin, Federica; Taddio, Andrea; Ventura, Alessandro; Barbi, Egidio (Arch Dis Child, 2017)

Phleboliths as a marker of slow-flow venous malformation. - Calligaris, Lorenzo; Berti, Irene; Barbi, Egidio (Arch Dis Child, 2015)

Paracetamol: a focus for the general pediatrician. - Marzuillo, Pierluigi; Guarino, Stefano; Barbi, Egidio (Eur J Pediatr, 2014)
UNLABELLED: Paracetamol (acetaminophen) is one of the most popular and widely used drugs for the treatment of pain and fever in children. This drug has multiple mechanisms of action, but its pharmacodynamic is still not well known. The central nervous system is the main site of action and it mirrors the paracetamol effect compartment. The recommended dosages and routes of administration should be different whether paracetamol is used for the treatment of pain or fever. For example, the rectal route, while being efficacious for the treatment of fever, should be avoided in pain management. Paracetamol is a safe drug, but some clinical conditions and concomitant drugs, which are frequent in clinical practice, may increase the risk of paracetamol toxicity. Therefore, it is important to optimize its administration to avoid overdoses and maximize its effect. The principal mediator of the paracetamol toxicity is the N-acetyl-p-benzo-quinone imine (NAPQI), a toxic product of the paracetamol metabolism, which could bind cysteine groups on proteins forming paracetamol-protein adduct in the liver. CONCLUSION: Although frequently prescribed, the concept of "effect compartment concentration" and the possible co-factors that could cause toxicity at recommended doses are not familiar to all pediatricians and general practitioners. We reviewed the literature concerning paracetamol mechanisms of action, we highlighted some relevant pharmacodynamic concepts for clinical practice, and we summarized the possible risk factors for toxicity at therapeutic dosages.
Keywords: Acetaminophen; Analgesics, Non-Narcotic; Child; Drug Overdose; Fever; Humans; Pain; Risk Factors

A precordial rub in a boy with a severe attack of ulcerative colitis. - Badina, Laura; Ferrara, Giovanna; Guastalla, Pierpaolo; Barbi, Egidio (Pediatr Emerg Care, 2014)
A case of a pneumomediastinum mimicking a pericarditis in a boy with an occult perforation due to ulcerative colitis is reported. Pneumomediastinum is a rare complication of severe attacks of ulcerative colitis, with or without the previous development of a toxic megacolon, that should be considered in the differential diagnosis.
Keywords: Adolescent; Colitis, Ulcerative; Diagnosis, Differential; Humans; Intestinal Perforation; Male; Mediastinal Emphysema; Pericarditis; Radiography, Thoracic

Procedural sedation for intra-articular corticosteroid injections in juvenile idiopathic arthritis (JIA) should be a standard of care. - Pastore, Serena; Gortani, Giulia; Taddio, Andrea; Barbi, Egidio (Eur J Pediatr, 2014)
Keywords: Arthritis, Juvenile; Conscious Sedation; Female; Glucocorticoids; Humans; Male; Pain; Patient Preference